Relationship of Advanced Paternal Age and Onset of Schizophrenia - Widyastuty, Arsusy; Gultom, Dapot P; Husada, Muhammad Surya (Sumatera Medical Journal, 2019)
Background: Increased paternal age has been associated with an increased risk of spontaneous abortion, premature birth, infant mortality, congenital malformations, childhood cancer, epilepsy, autism, bipolar and schizophrenia in offspring. The biological mechanisms behind this relationship are not known but may be associated with de novo mutations and epigenetic changes in male cells with short and long term health consequences for their offspring. Males are responsible for most of the new mutations in the gene group, to the permanent distribution of reproductive cells and the number of mutations increases significantly with age. Objective: The aim of the study to determine the correlation between paternal age and onset of schizophrenia. Method: This study was correlation analysis with cross sectional approach with The subject is 92 schizophrenia patient. Analysis of the data using statistical test that is chi-square. Result: the study findings showed there was significant correlation between paternal age with schizophrenic aged onset of 0.001 (p <0.05).